C57 DUAL ANTIPLATELET THERAPY DID NOT PREDICT ALL–CAUSE BLEEDING AT LONG–TERM FOLLOW–UP AFTER ACS: A SUBANALYSIS FROM THE APULIA PONTE ACS STUDY. (18th May 2022) - Citarelli, G; Locuratolo, N; De Martino, G; Resta, M; Sassara, M; Ricci, G; Cicala, M; Piscopo, A; Sanasi, M; Scicchitano, P; Lisi, F; Spadafina, T; et al.
Abstract: Background: Dual antiplatelet therapy (DAPT) has important implications for clinical outcomes in coronary disease. Nevertheless, the risk for bleeding often impact on the long–term administration of DAPT. The aim of this study was to evaluate the determinants of bleeding risk after ACS. Methods: This was a subanalysis of the PONTE ACS study. The PONTE ACS study is a prospective, longitudinal, cohort study which enrolled patients who were discharged from HUB centres of ASL BARI after coronary revascularization and/or ACS. They underwent clinical evaluation at 30 days, 3, 6 and 1 year–follow–up. The data were collected after including the data in the electronic medical record of the PONTE ACS study. Anthropometric, clinical and pharmacological parameters, instrumental and laboratory examinations were included. Data were computed in order to evaluate the major determinants of all–cause bleeding at one–year follow–up. Results: We finally enrolled 2476 patients (77.4% male, mean age: 67.2±12.0 years). Pharmacological treatments were optimized during the follow–up visits. According to anti–thrombotic therapies, 92.1% of patients persisted on DAPT at one–year follow–up. The number of patients on DAPT+anticoagulant were: 4.4%. All–cause bleeding occurred in 2.2% of patients. Anthropometric characteristics (height [β: –0.04594 ± 0.01610, p = 0.0044] and weight [β: –0.03043 ± 0.01035, p = 0.033]), male gender [β: –0.7008 ± 0.2818, p = 0.0129], and age [β: 0.02535 ± 0.01219, p = 0.0376] were the major determinants of all–cause bleeding at univariate regression analysis but they were not confirmed at multivariate regression analysis (p=ns). Kaplan Meier curve points out the impact of age on all–cause bleeding (Figure 1 ). Nor DAPT or triple therapy remained associated with all–cause bleeding at one year follow–up. Conclusions: Long–term DAPT is not a predictor of all–cause bleeding in patients who suffered ACS and/or coronary revascularization.